Analysis of 2016 LYS and YGS Physics Questions According to Bloom Taxonomy and Outcomes in the Curriculum - DURU, MEHMET KÜRŞAD (CUKUROVA UNIV, 2018)
In this study document analysis method which is one of the qualitative research methods is used in order to examine the physics questions in terms of the Bloom taxonomy and outcomes in the curriculum in LYS and YGS examinations conducted in 2016. The data of the research is composed of the YGS science test conducted on March 13th, 2016 and the LYS-2 physics test conducted on June 25th, 2016. The analysis of the questions was carried out in two stages. In the first stage, the physics questions asked in YGS and LYS were examined according to the outcomes in the secondary school physics and primary science and technology lessons curriculum (changes in the curriculum with the decision of the board dated 26/08/2011 and numbered 130) which is accepted by the board of education. In the second stage, physics questions were analyzed according to the revised Bloom taxonomy. The data obtained as a result of the analysis are presented as tables and are depicted with frequency values. When the physics questions in the YGS science test are examined, it is seen that five questions are asked about the outcomes in the 9th grade Physics curriculum. Six of the remaining eight questions were derived from primary education (6, 7, 8th grades) and the remaining two questions were derived from 10th and 11th grade physics program outcomes. Despite all candidates in YGS are responsible for common issues, asking questions from 10th and 11th grades show that these questions can only be solved by students taking elective physics courses.
Keywords: LYS and YGS Exam; Physics Questions; Bloom Taxonomy